Pastor A reader for ordained ministry - William H. Willimon (Nashville Abingdon Press, 2002)
An anthology of reflections on the tasks, joys, and challenges of ordained ministry, written by influential classical and contemporary thinkers.
Keywords: Pastoral Theology; Pastoral theology. Clergy -- Office. Pastorale theologie. Geestelijkheid. Pastores